Pengelolaan Digital Public Relation dalam Membangun Citra Positif Madrasah - Eka Diana; Siti Ratnatus Solehah; Siti Nadifah; Nazilatur Rohmah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
Educational institutions must be able to analyze the needs of the community. This study analyzes the management of digital public relations in building a positive image of madrasas implemented at MTs Az-Zainiyah I Randumerak. A qualitative approach and type of case study research used in this study. In collecting research data using several techniques, namely participant observation, in-depth interviews, and documentation studies. The research data consists of primary and secondary data, where primary data is obtained from research informants consisting of the head of the madrasah, the head of public relations, the head of administration, teachers. Meanwhile, primary data consists of national and international journals. The data analysis used consists of data reduction, data display, and conclusion drawing. The management of digital public relations in building a positive image of madrasah is carried out by involving public relations management functions consisting of planning, implementation, and control. The implementation of digital public relations only uses the Facebook platform in communicating with the community. The madrasah strategy in building a positive image is carried out starting with building opinions to marketing education.